Wavelength conversion based on four-wave mixing in a highly nonlinear fiber in ring configuration - Ahmad, Harith; Awang, Noor Azura; Latif, Amirah Abdul; Zulkifli, Mohd Zamani; Ghani, Zawajer A.; Harun, Sulaiman Wadi (IOP Publishing, 2011)
An efficient system for generating the four-wave mixing (FWM) effect in a short length of a highly nonlinear fiber (HNLF) is demonstrated using a ring configuration, which to our knowledge is the first of its kind to be reported. The conversion efficiency obtained is -4 dB for a HNLF length of 100 m when pumped with a 90 mW diode pump laser at 1490 nm in ring configuration which is the highest ever reported. The signal-to-noise (SNR) ratio is 43 dB. The conversion efficiency and SNR are flat over a span of 20 nm and can provide an effective means of wavelength conversion for telecommunication applications.